EXPLORING ENVIRONMENTAL CONCERN AND CONSUMER’S MOTIVES TOWARDS INTENTION TO PURCHASE ELECTRIC VEHICLE IN JAKARTA - Albert, Albert; Ruslim, Tommy Setiawan (Graduate Program of Universitas Tarumanagara, 2024)
In recent years, environmental damage has become a global problem. The cause of environmental damage is air pollution caused by various vehicle fuels, which produce CO2. This encourages people to care more about the environment, including the automotive industry. The rise of the environmental movement is encouraging car companies to produce electric vehicle products to reduce pollution. This research was conducted to determine and test the effects of environmental concerns, gain motives, and normative motives towards intention to purchase electric vehicle in Jakarta, and to test hedonic motivation as a mediator of gain motives and normative motives towards purchase intention. The study included 325 people living in Jakarta who either own or plan to own an electric car. This research use non-probability sampling techniques with the judgmental sampling method for sampling. The results of testing in this research used the PLS-SEM model with Smart-PLS system software version 4.0. The research results show that gain motives and normative motives have significant impact towards hedonic motives. Normative motives and hedonic motives have significant effects towards purchase intention. Environmental concern and gain motives have no significant impact towards purchase intention. Gain motives and normative motives influence purchase intention through hedonic motives.